The murine c-fgr gene product associated with Ly6C and p70 integral membrane protein is expressed in cells of a monocyte/macrophage lineage. - Hatakeyama, S (1994)
The c-fgr gene is a member of the Src family of protooncogene tyrosine kinases. A monoclonal antibody (2H2) that recognizes the specific region of the N-terminal domain of the murine c-fgr gene product (Fgr) has been established. With an immune complex kinase assay in a monocytic leukemia cell line, 2H2 monoclonal antibody was shown to precipitate a 59-kDa protein that corresponds in molecular mass to murine Fgr. Fgr was expressed highly in lymph nodes, slightly in spleen and peripheral blood leukocytes, and barely in the thymus and was not detected in bone marrow. In the presence of a mild detergent, Fgr was coimmunoprecipitated with a 70-kDa protein (p70) or with p70 plus several other molecules that were expressed on the cell-surface membrane of macrophage tumor cell lines PU5-1.8 and J774.1, respectively. By contrast, Fgr was not coimmunoprecipitated with a low-affinity receptor for the Fc portion of IgG that is associated with human Fgr. The molecule was also coimmunoprecipitated with the Ly6C molecule from a macrophage cell line (J774.1) that showed protein-tyrosine kinase activity. Peptide mapping revealed that this kinase activity was derived from Fgr. The similarity of relationship between this intramembrane p70 and/or Ly6C and cytoplasmic Fgr to relationships previously reported between T-cell antigen receptor complex, including CD4 and CD8 coreceptors, and Lck or Fyn in T cells and between surface IgM and Lyn or Blk in B cells, suggests that the Fgr and p70 or Ly6C are, indeed, associated with each other and in the murine system may be responsible for recognition of extracellular substances (either cellular or noncellular) and for signal transduction in cells of monocyte/macrophage lineage.